PELAKSANAAN FUNGSI KELUARGA BAGI PASANGAN YANG BERTEMPAT TINGGAL TERPISAH DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Anggun Febria Merlina; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The basic function of the family is to provide suitable environmental conditions for family members so that the physical, psychological, social and mental aspects of all family members can develop family function relates to how all family members communicate, form relationships, maintain relationships, make decisions, and solve problems together. Related to this research, the family institution that is in it of course has family functions that must continue to run, such as: educational function, socialization function, economic function, and also sexual function. This study serves to describe how the implementation of family functions for couples who live separately in Gunung Toar District, Kuantan Singingi Regency. This study uses a descriptive qualitative research method. The subjects selected in this study were four informants. Data collection techniques using observation, documentation, and in-depth interviews. The results of research on the implementation of family functions are going well, from the economic factors in this family (building a house and giving monthly money goes well) every wife feels that her husband is giving her enough economic support. Keywords: Family Funcation, Family Characteristic, Family Needs